2019
DOI: 10.1016/j.dark.2019.100377
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations of the LHC Dark Matter Working Group: Comparing LHC searches for dark matter mediators in visible and invisible decay channels and calculations of the thermal relic density

Abstract: Weakly-coupled TeV-scale particles may mediate the interactions between normal matter and dark matter. If so, the LHC would produce dark matter through these mediators, leading to the familiar "mono-X" search signatures, but the mediators would also produce signals without missing momentum via the same vertices involved in their production. This document from the LHC Dark Matter Working Group suggests how to compare searches for these two types of signals in case of vector and axial-vector mediators, based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
115
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 86 publications
(117 citation statements)
references
References 76 publications
2
115
0
Order By: Relevance
“…Much of previous work has considered "s-channel models" in which the mediator is a dark force carrier, a neutral boson which has interactions both with a pair of dark matter particles and with a pair of Standard Model particles [2][3][4][5]. While interesting parameter space remains to be explored, such constructions are generically constrained by searches for visible decays of the mediator [6,7]. A different, and equally compelling class of models contains colored mediator particles, which can either interact directly with a quark and a dark matter particle [8][9][10][11][12][13][14][15], or act as a bridge at loop level between a pair of dark matter particles and a pair of gluons [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Much of previous work has considered "s-channel models" in which the mediator is a dark force carrier, a neutral boson which has interactions both with a pair of dark matter particles and with a pair of Standard Model particles [2][3][4][5]. While interesting parameter space remains to be explored, such constructions are generically constrained by searches for visible decays of the mediator [6,7]. A different, and equally compelling class of models contains colored mediator particles, which can either interact directly with a quark and a dark matter particle [8][9][10][11][12][13][14][15], or act as a bridge at loop level between a pair of dark matter particles and a pair of gluons [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…In this model the Z width can easily be large compared to the detector resolution and therefore large enough for interference effects to be relevant. As a specific benchmark we considered g χ = 1, g q = 0.1, and g = 0.01 (a choice recommended by the LHC Dark Matter Working Group and used by both ATLAS and CMS to present exclusion limits [42]), as well as an additional example with g = 0.02. Deriving bounds on this model as a function of DM mass and mediator mass, we demonstrated that interference effects lead to substantially stronger constraints on the parameter space of this model (see figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…Such large widths typically cannot be obtained from decays into SM particles (as the required couplings would violate experimental constraints), but they are a generic prediction in models with additional contributions to the Z width arising from decays into new invisible light degrees of freedom. As a specific example of such a model, we consider a spin-one simplified DM model [23], which has been employed by the LHC collaborations [41,42] to create benchmark points in theory space that allow for different LHC DM searches to be compared to each other and to non-collider experiments.…”
Section: Bounds On Dark Matter Simplified Modelsmentioning
confidence: 99%
See 2 more Smart Citations